Analisis Penyebaran Penularan Virus Covid-19 di Provinsi Jawa Barat Menggunakan Algoritma K-Means Clustering - Darmansah Darmansah Darmansah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Covid-19 or Corona Virus is a virus that emerged at the end of 2019. This virus is spreading rapidly in various countries in the world. Currently, almost all countries in the world are reported to have been infected by this new type of virus. This corona virus was first discovered in China and until now in a major country in the world, there is no Indonesian country. All provinces in Indonesia have now been exposed to the Covid-19 virus starting from March 2020. One of the provinces most exposed to Indonesia is West Java province. The covid-19 virus has spread in various cities and districts in West Java. To make it easier for the West Java regional government to make decisions on preventing the spawning of the Covid-19 virus, it is necessary for researchers to determine the level of spread of Covid-19 transmission which is divided into three clusters. The first cluster is C0 with the high category, C1 with the medium category and C2 with the low spread category. In the analysis of the spread of the covid-19 virus, the researchers used data mining methods and the K-Means Clustering algorithm to classify the distribution data. Then in data processing researchers use the Rapidminer Studio 7.6 application. From the results of this study, it was found that C0 there were 18 cities / districts, C1 there were 1 city / regency and C2 there were 16 cities / districts where the Covid-19 virus was spreading in West Java province.